Designing Context-Aware Construction Systems - Brandão, Filipe J.S. (Utopian Possibilities: Knowledge, Happiness & Wellbeing, 2021)
The idea of using digital frameworks to support user-participation in the design of the built environment, which can be traced back to the sixties, is (re)gaining momentum with developments in AI, computational design, and digital fabrication. In a sense it is the reframing of the modernist utopia of providing affordable housing at scale, by replacing the traditional paternalistic top-down design method with co-design methods implemented in digital systems to provide context specific solutions to users. Covid-19 has contributed to accelerate the above digitalization trends, with consequences such as a transition to home-working, long foreseen by authors such as Alvin Toffler. This transition will affect all aspects of the built environment from the way cities and houses are organized to very nature of construction. Moving work back to the home will likely increase the frequency of interior renovations which already accounts for a large portion of the carbon emissions over the building’s life. The above trends and the contemporary context of climate emergency require a fundamental shift in how buildings are procured, designed, constructed, (re)used and demolished. The urgency of the matter calls for open innovation to develop building systems for local contexts based on sustainability criteria. Open-source digital frameworks to enable the design, fabrication, delivery and reuse of systems, components and materials must be imagined and implemented (Ratti & Claudel, 2015, p. 10). The present article details design principles for mass-customizable and disassembleable construction systems of partition walls.